METHODOLOGY OF FORMING UNITS OF LENGTH MEASUREMENT IN CLASS 1-2 MATHEMATICS LESSONS - Saydaliyeva L. M. (Galaxy International Interdisciplinary Research Journal, 2023)
The article talks about the method of forming units of measurement of length in 1-2 grade mathematics classes.